DESIGNING AN ESP COURSE ACCORDING TO WHAT STUDENTS WANT AND NEED. AN ANALYSIS OF STUDENTS’ NEEDS AND EXPECTATIONS - NISTOR (GÂZ), Roxana-Maria (Studia Universitatis Babeș-Bolyai Philologia, 2019)
Designing and ESP course according to what students want and need. An analysis of students’ needs and expectations. Starting from the premise that, in designing a course of English for Specific Purposes, the language instructor should also check and take into account what students want, the purpose of this article is to present information about the proficiency and diagnostic test and the needs analysis questionnaire applied to some first-year students enrolled at the Faculty of European Studies within Babeș-Bolyai University. The findings of our study showed the needs and the problems of our students, and revealed that they want to improve their communication, grammar, and writing skills, but they also want the English course to be enjoyable and to focus on various specialised topics, not only on their specific field of study. REZUMAT. Elaborarea unui curs de limba engleză pentru scopuri specifice în funcție de ceea ce studenții doresc și le este util. O analiză a nevoilor și așteptărilor studenților. Pornind de la premisa că, în elaborarea unui curs de limba engleză pentru scopuri specifice, profesorul de limbă trebuie să verifice și să ia în considerare și ceea ce își doresc studenții, prezentul articolul își propune să prezinte informații referitoare la testul inițial și la chestionarul privind analiza de nevoi aplicate studenților din anul întâi înscriși la Facultatea de Studii Europene din cadrul Universității Babeș-Bolyai. Rezultatul studiului nostru evidențiază problemele cu care se confruntă studenții, nevoile acestora, precum și faptul că aceștia vor să își îmbunătățească abilitățile de comunicare, gramaticale și de scriere în limba engleză și că își doresc să participe la un curs de limbă care să fie plăcut și care să se concentreze pe diferite teme de specialitate, nu doar pe cele specifice domeniului lor de studiu. Cuvinte-cheie: test ințial, analiză de nevoi, chestionar, engleză pentru scopuri specifice, designul cursului, studii europene, abilități.